2007
DOI: 10.1007/s10562-007-9182-x
|View full text |Cite
|
Sign up to set email alerts
|

A Cu/Zn/Al/Zr Fibrous Catalyst that is an Improved CO2 Hydrogenation to Methanol Catalyst

Abstract: A series of Cu/Zn/Al/Zr CO 2 hydrogenation to methanol catalysts containing different ratios of Al/Zr were prepared using a co-precipitation procedure. SEM, TEM, and XRD characterization showed that all the catalysts comprised crystallites in a fibrous structure and their Cu/Zn crystallite dispersions were better than that of a commercial (COM) catalyst. It is suggested that the high dispersion and stability of the Cu/Zn crystallites due to the fibrous structure enhanced CO 2 hydrogenation, and the added Zr co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 22 publications
6
59
0
Order By: Relevance
“…Both are regarded as effective components [17] that affect the microstructure so that the activity and stability are greatly improved. This was also verified in our previous study [18]. In addition, the microscopic morphology of a Cu-based catalyst before and after deactivation has been characterized by transmission electron microscopy (TEM) [19].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Both are regarded as effective components [17] that affect the microstructure so that the activity and stability are greatly improved. This was also verified in our previous study [18]. In addition, the microscopic morphology of a Cu-based catalyst before and after deactivation has been characterized by transmission electron microscopy (TEM) [19].…”
Section: Introductionsupporting
confidence: 83%
“…The CuZnAlZrMn catalyst had an activity that was only better than CuZn. This result indicated that Al and Zr are excellent promoters in improving the activity for methanol synthesis, and the ratio of 1:1 of the two promoters in the CuZnAlZr catalyst is the best [18]. The addition of Al or Zr gave a better catalytic performance.…”
Section: Catalytic Activitymentioning
confidence: 86%
See 1 more Smart Citation
“…[49][50][51][52] In view of our present understanding of the mechanism of the syngas based chemistry, this is not unexpected. Although still debated, it is now usually accepted that methanol is formed almost exclusively by hydrogenation of CO 2 contained in the syngas on the catalyst's surface.…”
mentioning
confidence: 83%
“…172 Because of the high stability under reducing or oxidizing atmospheres, zirconia has also been considered as an excellent promoter or support for the methanol synthesis catalyst. 151,156,163 Catalytic activity and selectivity toward methanol are both improved due to the enhanced copper dispersion in the presence of ZrO 2 . 151,159,160,174,175 In addition, the crystal types of zirconia influence performance of the catalyst.…”
mentioning
confidence: 99%